Caracterización y propuesta técnica de la acuicultura en el sector de la parroquia rural santa rosa de flandes del canton naranjal, provincia del Guayas, republica del Ecuador. - Arias, Faustino (2010)
Santa Rosa de Flandes, a rural site part of Naranjal, in Guayas Province, has been for almost 20 years an important center for Aquaculture in the country. This zone is a confluence of several agriculture projects, shrimp farms, crab fisheries and ecological conservation. As other Aquaculture sites in the country, the shrimp farms located in this location, tried several techniques for farming other species which finally adapted to their geography, climate with the purpose of proposing strategies to conserve this activity and to not interfere with other productivity units to ensure the survival of the Aquaculture.